Evaluasi Kapasitas dan Jangkauan Pelayanan Fasilitas Pendidikan Sekolah Menengah Pertama dan Madrasah Tsanawiyah di Kota Surakarta - Sakti Arya Wiseka; Yuniaristanto .; Muhammad Hisjam (Industrial Engineering, Faculty of Engineering, Universitas Sebelas Maret, 2018)
Improving the quality of education is important for human beings and also an important issue for municipal government. The balance between the amounts of educational facility needs with the availability of facilities is a problem in the education sector. Surakarta is one of the towns in Indonesia, which has the highest population density in Central Java Province. Therefore, it is necessary to evaluate the amount of capacity of existing educational facilities. This research uses Capacitated Max Covering model which runs using IBM ILOG CPLEX software. Further obtained results were based on the capacity of existing educational facilities today, can be met optimally. However, it is necessary to increase the capacity of schools or addition of new educational facilities to accommodate students who have not received school quotas within the city.